Effect of retarders on the early hydration and mechanical properties of reactivated cementitious material. (10th July 2019) - Zhang, Linglei; Ji, Yongsheng; Li, Jun; Gao, Furong; Huang, Guodong
Highlights: The retarding effects of different retarders on DCRCM are variable. Borax can effectively reduce initial hydration rate and increase setting time. The best mechanics properties can be obtained when borax amount is 2%. The mechanism for retarding effect of borax on DCRCM paste is analyzed. Abstract: Effects of different retarders (gypsum, sodium citrate, sodium gluconate and borax) on setting and hardening behaviors of dehydrated cement paste (DCP) composite reactivated cementitious materials (DCRCM) are studied through determinations of setting time and mechanical properties. Mechanism of Early hydration and hardening is also studied based on hydration kinetics and SEM analysis. The results indicate that sodium citrate and gypsum are of poor retarding effect on DCRCM. Proper amount of borax will effectively retard the setting process. Sodium gluconate is of best retarding effect, whereas it will result in low early strength of DCRCM. When used as a retarder, borax is of obvious retarding effect. It can not only effectively restrain initial hydration process of DCRCM, but also accelerate early hardening process of DCRCM, promoting the establishment and development of mechanics strength. When the mixing amount of borax is 2%, both early and late strengths of DCRCM can reach to the maximum. SEM analysis shows that the hardening paste of DCRCM with borax is characterized by dense microstructure and less defects, greatly improving the mechanical properties of DCRCM.